(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The article is devoted to the substantiation of the need to manage the quality of human resources in a university in the context of reforming the higher education system. The changes that have taken place in the system of higher education are considered. The factors influencing the need for quality management of human resources in the university are determined. The elements of the system and the stages of the quality management process of the human resources of the university are described. It is shown that the efficiency and competitiveness of the university largely depend on the quality management of human resources.